The FPBA algorithm with controlled capture ICC2001 - Habaebi, Mohamed Hadi; Mohd Ali, Borhanuddin (2001)
Abstract-In this paper, we introduce a new mixed priority scheme that utilizes the LESRTPL model [S] to control the assignment of the transmitter power levels, assigned to each priority class, whose contending over the wireless channel using the FPBA algorithm [l] to capture the channel. The wireless channel capture model includes Rayleigh fading, shadowing, and path loss. The performance of the algorithm is evaluated using simulation models. Results show that the new priority scheme offers significant improvement to the throughput and the waiting time of the different priority classes, especially to high priority class packets.